If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + 5 + 8p + -16 + q = 0 Reorder the terms: 5 + -16 + 3p + 8p + q = 0 Combine like terms: 5 + -16 = -11 -11 + 3p + 8p + q = 0 Combine like terms: 3p + 8p = 11p -11 + 11p + q = 0 Solving -11 + 11p + q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11p + 11 + q = 0 + 11 Reorder the terms: -11 + 11 + 11p + q = 0 + 11 Combine like terms: -11 + 11 = 0 0 + 11p + q = 0 + 11 11p + q = 0 + 11 Combine like terms: 0 + 11 = 11 11p + q = 11 Add '-1q' to each side of the equation. 11p + q + -1q = 11 + -1q Combine like terms: q + -1q = 0 11p + 0 = 11 + -1q 11p = 11 + -1q Divide each side by '11'. p = 1 + -0.09090909091q Simplifying p = 1 + -0.09090909091q
| 7y+1=5y-1+2y | | 6y+5=4y+5+2y | | 8=-5k-12 | | 5m+5=-3+5m-1-3m | | 3x+6+7x=-104 | | 0.46-0.15x=0.2-0.1 | | 180=(2x+10)+(65-x) | | 3(1-2n)+10=-4(2n-3) | | 4(5t+4)= | | r^2=50.92 | | 4(5t+4)90= | | 4(h-6)+h=3 | | 5(2y-3)=-2(3y+2y) | | 5(3x+7)=15 | | 6x+14-3x=7x-10-2x | | 4(n-3)=-6(2n+1) | | (6x^3+8x^2)-3x^2= | | 2(f+1)=3(2f-1) | | 3(c-12)=4-c | | x+(x+6)+x+(x+6)=20 | | x+2x+x+2x=66 | | 1/8x=1/6 | | 9+(1)-9= | | 42+-2d=6 | | -(x+9)=10 | | p/3-p/7=4 | | 0.8k=-0.2k-3 | | -4x+7=-31 | | 2m+5-2(m+7)= | | 2y-5=10-8y | | c+12=4c-6 | | -6x-9=45 |